Differential Effects of Dietary Supplementation with Fish Oil or Soy Lecithin on Human Platelet Adhesion - Andrioli, Giuseppe; Carletto, Antonio; Guarini, Patrizia; Galvani, Simonetta; Biasi, Domenico; Bellavite, Paolo; Corrocher, Roberto (Thrombosis and Haemostasis, 1999)
To investigate the possible regulating role of ω-6 and of ω-3 fatty acids on platelet adhesiveness, we randomised 60 volunteers into three groups to take 20 ml (equivalent to 0.3 g ω-6, 3.6 g ω-3; ω-6/ω-3 ratio 0.1) per day of a fish oil supplement, or to take 25 g (equivalent to 1.5 g ω-6, 0.5 g ω-3; ω-6/ω-3 ratio 3) per day of a soy lecithin supplement, or to continue on their usual diet without any supplement (control group) for a period of 15 days. Platelet adhesion on fibrinogen-coated 96-well microtitre plates was evaluated in the resting condition and after stimulation with 2 ωM ADP or 0.02 U/ml thrombin. Compared to the values before the experimental period, the fish oil group showed a significant reduction in stimulated adhesion (with ADP: from 18.8% to 15.6%, p <0.01; with thrombin: from 24.4% to 20.8%, p <0.005), whereas no difference was noted in the resting condition (from 3.6% to 3.5%, NS). In the soy lecithin group, platelet adhesion was increased in all test conditions (with ADP: from 18.7% to 23.2%, p <0.001; with thrombin: from 24.0% to 29.9%, p <0.001; resting: from 3.5% to 6.6%, p <0.001). No significant changes were observed in the control group. A good correlation was found between platelet adhesion data and the changes in the platelet fatty acid ω-6/ω-3 ratio caused by the different supplementations. Our results indicate an inhibitory effect of fish oil rich in ω-3 fatty acids on stimulated human platelet adhesiveness and a stimulatory effect of soy lecithin rich in ω-6 fatty acids on resting and stimulated adhesion. They suggest moreover that the ω-6/ω-3 ratio is a determinant of platelet adhesion.
Keywords: Fatty acid; adhesion; platelet; thrombosis